Peranan Kantor Urusan Agama Dalam Meminimalisir Terjadinya Perkawinan di Bawah Umur di Kecamatan Medan Barat - Adenan Adenan; Sarmalina Pane; Muhammad Syafrizal (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
A marriage that involves one or both partners before the woman is physically, physiologically, and psychologically prepared to support the responsibilities of marriage and parenthood is referred to as an underage marriage. Early marriage is an underage marriage whose aim preparation is not said to be maximal in terms of physical preparation, mental preparation, as well as material preparation, given the general age limit for marrying at a legal age. This article will delve more into the Office of Religious Affairs' contribution to reducing underage weddings. The aim of this essay is to provide writers and readers with a clearer understanding of the KUA's function in reducing the number of underage marriages in the Medan Barat District. This article employs a descriptive analysis strategy along with a qualitative research methodology. The Office of Religious Affairs (KUA), in the author's opinion, is crucial in preventing and reducing the number of underage marriages in the Medan Barat District. The Office of Religious Affairs works to prevent underage marriages in the West Medan District by, among other things, giving advice and counseling to prospective brides before their weddings. The West Medan District's junior high school pupils were adversely affected by early marriage, according to KUA of the West Medan Sub-District, which also conducted outreach on the laws governing underage marriage. Keywords: Office of Religious Affairs, Marriage, Minors